Aristotelian ethics in contemporary perspective - Peters, Julia (Routledge Studies in Ethics and Moral Theory, 2013)
By bringing together influential critics of neo-Aristotelian virtue ethics and some of the strongest defenders of an Aristotelian approach, this collection provides a fresh assessment of the strengths and weaknesses of Aristotelian virtue ethics and its contemporary interpretations. Contributors critically discuss and re-assess the neo-Aristotelian paradigm which has been predominant in the philosophical discourse on virtue for the past 30 years